Polymer powder adhesion to metallic surface improvement with plasma - Hladík, J.; Píchal, J.; Špatenka, P. (Вопросы атомной науки и техники, 2008)
Useful method for corrosion prevention is coating of a base material with a suitable substance. It performs a barrier between the base material and its environment. Great attractions in this field have found polymers, among them polyethylenes (PE). Due to the low adhesion grade of unmodified polymer powder or granules the application of any modification process increasing the adhesion grade is crucial. At present there is no universal approach to polymer adhesion improvement and there have been employed various quite different techniques. Our research employed the PE adhesion improvement by plasma modification. There were used two plasma reactors – the microwave low pressure reactor and the atmospheric reactor employing dielectric barrier discharge (DBD). The adhesion of the powder was determined by measurement of strength force demanded for displacement of the PE-metal joint. Ефективним методом запобігання корозії є покриття вихідного матеріалу підходящою субстанцією. Остання утворить бар'єр між вихідним матеріалом і навколишнім середовищем. Велику привабливість у цьому напрямку одержали полімери, зокрема, поліетилени (ПЕ). Важливим є застосування будь-якого методу модифікації, що підвищує низький рівень адгезії полімерного порошку або гранул. В даний час немає універсального методу поліпшення адгезії полімерів і для цих цілей використовується дуже різноманітне устаткування. Ми досліджували збільшення адгезії ПЕ під впливом плазми. Були використані два плазмових реактори – мікрохвильовий реактор низького тиску й атмосферний реактор з діелектричним бар'єрним розрядом (ДБР). Адгезія порошку визначалася за допомогою виміру силового навантаження, необхідної для руйнування з'єднання ПЕ- метал. Эффективным методом предотвращения коррозии является покрытие исходного материала подходящей субстанцией. Последняя образует барьер между исходным материалом и окружающей средой. Большую привлекательность в этом направлении получили полимеры, в частности, полиэтилены (ПЭ). Важным является применение какого-либо модифицирующего метода повышения низкого уровня адгезии полимерного порошка или гранул. В настоящее время нет универсального метода улучшения адгезии полимеров и для этих целей используется очень разнообразное оборудование. Мы исследовали увеличение адгезии ПЭ под воздействием плазмы. Были использованы два плазменных реактора – микроволновый реактор низкого давления и атмосферный реактор с диэлектрическим барьерным разрядом (ДБР). Адгезия порошка определялась с помощью измерения силовой нагрузки, требуемой для разрушения соединения ПЭ- металл.